A longitudinal evaluation of family caregivers' willingness to pay for an in-home nonpharmacologic intervention for people living with dementia: results from a randomized trial. (24th April 2021) - Jutkowitz, Eric; Pizzi, Laura T.; Popp, Jonah; Prioli, Katherine K.; Scerpella, Danny; Marx, Katherine; Samus, Quincy; Piersol, Catherine Verrier; Gitlin, Laura N.
Abstract: Objective: To determine the willingness-to-pay (WTP) of family caregivers to learn care strategies for persons living with dementia (PLwD). Design: Randomized clinical trial. Setting: Community-dwelling PLwD and their caregivers (dyads) in Maryland and Washington, DC. Participants: 250 dyads. Intervention: Tailored Activity Program (TAP) compared to attention control. TAP provides activities tailored to the PLwD and instructs caregivers in their use. Measurement: At baseline, 3 and 6 months, caregivers were asked their WTP per session for an 8-session 3-month in-home nonpharmacologic intervention to address behavioral symptoms and functional dependence. Results: At baseline, 3 and 6 months, caregivers assigned to TAP were willing to pay 26.10/session (95%CI:20.42, 33.00), 28.70 (95%CI:19.73, 39.30), and 22.79 (95%CI: 16.64, 30.09), respectively; attention control caregivers were willing to pay 37.90/session (95%CI: 27.10, 52.02), 30.92 (95%CI: 23.44, 40.94), 27.44 (95%CI: 20.82, 35.34), respectively. The difference in baseline to 3 and 6 months change in WTP between TAP and the attention control was 9.58 (95%CI: −5.00, 25.47) and 7.15 (95%CI: −5.72, 21.81). The difference between TAP and attention control in change in the proportion of caregivers willing to pay something from baseline to 3 and 6 months was −12% (95%CI: −28%, −5%) and −7% (95%CI:−25%, −11%), respectively. The difference in change in WTP, among caregivers willing to pay something, between TAP and attention control from baseline to 3 and 6 months was 17.93 (95%CI: 0.22, 38.30) and 11.81 (95%CI: −2.57, 28.17). Conclusions: Family caregivers are willing to pay more for an intervention immediately following participation in a program similar to which they were asked to value.